The Reception of the Hebrew Prophets in Ancient Christianity - Riemer Roukema (Religions, 2022)
This contribution discusses the ways in which the Hebrew prophets in Greek and Latin translations were received by Christians from the second to fifth centuries CE, preceded by an impression of the New Testament use of these prophets. Besides the vast amount of ecclesiastical references and commentaries, it also deals with Marcionite and Gnostic views. It demonstrates that Christians most often read the prophets as testimonies to Christ and the communities of those who believed in him. Allegorical readings came up soon and were justified by Origen of Alexandria (185–254 CE), whose interpretations were most influential in subsequent centuries. In the fourth century, a reaction against the allegorical reading of the prophets arose in Antioch, Syria; the “Antiochene school” rather limited its approach to the historical context of the prophets, except for texts read Christologically in the New Testament. This article also considers the question whether the Christian appropriation of the Hebrew prophets may be deemed legitimate.